The Math Problems Notebook - Boju, Valentin; Funar, Louis (Birkhäuser Boston : Imprint: Birkhäuser, 2007)
The Math Problems Notebook is a collection of nontrivial, unconventional problems requiring deep insight and imagination reminiscent of those discussed at Sunday Math Circles. These circles have become a place for disseminating beautiful mathematics at an elementary level for college students who have a common passion for mathematics. The problems cover many topics, including number theory, algebra, combinatorics, geometry and analysis, of varying levels of difficulty. The presentation of each topic begins with simple exercises and follows with more difficult problems, challenging enough even for the experienced problem solver. The easier problems focus on basic methods and tools, while the more advanced problems develop problem-solving techniques, intuition and promote further research. Undergraduates and teachers of advanced mathematics, as well as the casual mathematician will mutually enjoy The Math Problems Notebook.